Protective effects of melatonin on myocardial ischemia/reperfusion induced infarct size and oxidative changes - Sahna, E; Parlakpinar, H; Turkoz, Y; Acet, A (Physiological research, 2005)
Free radicals, calcium overloading and loss of membrane phospholipids play an important role in the development of ischemia/reperfusion (I/R) injury. Melatonin is a well-known antioxidant and free radical scavenger. Melatonin may also reduce the intracellular calcium overloading and inhibit lipid peroxidation. This study was designed to investigate the effects of melatonin on the I/R-induced cardiac infarct size in an in vivo rat model. We also investigated glutathione (GSH) levels, an antioxidant the levels of which are influenced by oxidative stress, and malondialdehyde (MDA) levels, which is an index of lipid peroxidation. To produce cardiac damage, the left main coronary artery was occluded for 30 min, followed by 120 min reperfusion, in anesthetized rats. Melatonin (10 mg/kg) or vehicle was given 10 min before ischemia via the jugular vein. Infarct size, expressed as the percentage of the risk zone, was found significantly greater in I/R group than in the melatonin-treated I/R group. MDA levels were significantly higher, but GSH levels were lower in the I/R group than in the control group. Melatonin significantly reduced the MDA values and increased the GSH levels. These results suggest that oxidative stress contributes to myocardial I/R injury and melatonin administration exerts a mitigating effect on infarct size. Furthermore, the results indicated that melatonin improves the antioxidant capacity of the heart and attenuates the degree of lipid peroxidation after I/R.
Keywords: Animals; reperfuzní poškození; kardiotonika; glutathion; oxidační stres; Rats, Wistar; Melatonin; Glutathione; výsledek terapie; Oxidative Stress; Treatment Outcome; stupeň závažnosti nemoci; Male; Malondialdehyde; Reperfusion Injury; melatonin; Myocardial Infarction; krysa rodu Rattus; Cardiotonic Agents; malondialdehyd; mužské pohlaví; zvířata; Severity of Illness Index; Rats; infarkt myokardu; potkani Wistar